Suture Tape-Augmented Posterior Cruciate Ligament Repair Should Be Tensioned and Fixed at Approximately 100° Knee Flexion to Prevent Loss of Full Flexion - Roger Ostrander, M.D; Steve Jordan, M.D; John Konicek; William Baldwin, M.D (Elsevier, 2021)
Purpose: To evaluate the biomechanics of simulated posterior cruciate ligament injuries (SimPCL) with and without internal brace suture tape augmentation (IBSTA) in cadaver knees. Methods: A total of 20 cadaveric knees were used, all male, with an average age of 65 ± 18 years. Femoral tunnel isometry was evaluated at the 1/11 o'clock and 2/10 o'clock femoral positions. SimPCL were created in 6 knees. IBSTA was performed, and load data were collected through knee range of motion. An additional 6 specimens were evaluated at the 1/11 femoral tunnel position, and load cell recordings were obtained at 10 different knee flexion angles. Cyclic displacement in 8 cadaver knees was assessed using an Instron machine. Load and displacement data were recorded. Testing was performed under 3 conditions for each specimen: intact PCL, SimPCL, and SimPCL/IBSTA using the 1/11 femoral tunnel position. Results: There was no difference in isometry when comparing the 1/11 o'clock (7.1 ± 4.0 ft∗lb) femoral position and the 2/10 o'clock (7.6 ± 4.2 ft∗lb) position (P = .467). SimPCL/IBSTA suture tape tension gradually increased with progressive flexion to a peak at approximately 120° of knee flexion. For cycle 100 tibial displacement, there was no difference between intact (4.41 mm) and SimPCL/IBSTA (5.59 mm, P = .391). There was a difference between intact (4.41 mm) and SimPCL (7.19 mm, P = .006) , but there was no significant difference between SimPCL/IBSTA (5.59 mm) and SimPCL (7.19 mm, P = .140). There was a difference in cycle 1 stiffness between intact (62.3 N/mm) and Sim2PCL (37 N/mm, P = .005). There was no difference between other groups. Conclusions: In this cadaver study, there was a 1.18-mm average difference in posterior tibial displacement when comparing intact and SimPCL/IBSTA. The internal brace construct should be tensioned and fixed at approximately 100° of knee flexion to prevent loss of full flexion. Clinical Relevance: The presented biomechanical data for internal bracing of PCL injuries may lead to improved surgical techniques.